2017
DOI: 10.1080/10503307.2017.1330574
|View full text |Cite
|
Sign up to set email alerts
|

General and specific factors of working alliance in parent training: A bifactor exploratory structural equation modelling approach

Abstract: The Working Alliance Inventory Short form (WAI-S) comprises 12 items that measure 3 subdomains (goal, task, and bond). In the present study, we evaluated the factor structure of WAI-S in a parent management training (PMT) context, by investigating a series of different factor models, including standard confirmatory factor analyses (CFA) models and more recent alternatives, like the exploratory structural equation model (ESEM), the bifactor-CFA, and the bifactor exploratory structural equation model (B-ESEM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In total, four out of 51 studies reported an adequate model fit, according to the COSMIN criteria for sufficient structural validity (Hatcher et al, 1995;Toste et al, 2015;Hukkelberg and Ogden, 2017;Knowles et al, 2020). The study of Hatcher et al (1995) confirmed a three-factor structure (bond, task, and goal) as the best-fitting model; however, the methodological quality of this study was inadequate because of its small sample size.…”
Section: Structural Validitymentioning
confidence: 69%
See 4 more Smart Citations
“…In total, four out of 51 studies reported an adequate model fit, according to the COSMIN criteria for sufficient structural validity (Hatcher et al, 1995;Toste et al, 2015;Hukkelberg and Ogden, 2017;Knowles et al, 2020). The study of Hatcher et al (1995) confirmed a three-factor structure (bond, task, and goal) as the best-fitting model; however, the methodological quality of this study was inadequate because of its small sample size.…”
Section: Structural Validitymentioning
confidence: 69%
“…The criteria for sufficient internal consistency are a Cronbach's alpha ≥ 0.70 and at least low evidence for sufficient structural validity (sufficient validity = sufficient model fit, tested with confirmatory factor analyses or IRT/RASH analyses). Only one study met both criteria for internal consistency (Hukkelberg and Ogden, 2017). In 64 different analyses of the WAI and its adapted versions a Cronbach's alpha > 0.70 was found.…”
Section: Internal Consistencymentioning
confidence: 94%
See 3 more Smart Citations